The effect of a daytime 60-min nap opportunity on postural control in highly active individuals - Ammar, A.; Boukhris, O.; Hsouna, H.; Ben Dhia, I.; Trabelsi, K.; Gujar, T. A.; Clark, C. C. T.; Chtourou, H.; Driss, T.; Hoekelmann, A. (Biology of Sport, 2021)
Although napping is commonly used as a strategy to improve numerous physical and cognitive performances, the efficacy of this strategy for improving postural balance has not yet been elucidated. Thus, the aim of this study was to conduct a comprehensive examination of the effect of a 60 min nap opportunity (N60) on different components of postural control. Ten highly active individuals (age = 27 ± 3.5 y, height = 1.75 ± 0.52 m, weight = 66.02 ± 8.63 kg) performed, in a randomized order, two afternoon test sessions following no nap (NN) and N60. Postural balance was assessed using the sensory organisation test (SOT), the unilateral stance test (UST), and the limits of Stability Test performed on NeuroCom® Smart Balance Master. The subjective rating of sleepiness before and after the nap conditions was also assessed. Compared to NN, N60 improved the composite balance score (p < 0.05, ES = 0.75, delta = 5.3%) and the average and maximum percentage balance in the most challenging postural conditions of the SOT (p < 0.05 for SOT-4 and 5 and p < 0.0005 for SOT-6; ES range between 0.58 and 1.1). This enhanced postural balance in N60 was accompanied with improved visual (p < 0.05; ES = 0.93; delta = 8.9%) and vestibular (p < 0.05; ES = 0.81; delta = 10.5%) ratios and a reduced level of sleepiness perception (p < 0.001, ES = 0.87). However, no significant differences were found in any of the UST and LOS components` scores (p > 0.05). Overall, a 60 min post lunch nap opportunity may be viable for improving static balance, although further work, involving larger samples and more complex motor activities, is warranted.